Answer:
![(-2,(3)/(2))](https://img.qammunity.org/2021/formulas/mathematics/high-school/8lmdklj3871xf08kg0plvqbifu206lubpd.png)
Explanation:
To find the midpoint, simply use the Midpoint Formula.
The Midpoint Formula states that for two points
and
, the midpoint will be:
.
So, here,
= (-2, -1) and
= (-2, 4). The midpoint is then:
![((-2+(-2))/(2) ,(-1+4)/(2) )=((-4)/(2) ,(3)/(2) )=(-2,(3)/(2))](https://img.qammunity.org/2021/formulas/mathematics/high-school/fo9ptm2v5yxpcejqom84gwyn3xw8xq17a2.png)
Thus, the answer is
.
Hope this helps!